Boolean network attractor regulation and control method, device and equipment and storage medium - HU QINGSONG; HAN HUAXIANG (2024)
The invention provides a Boolean network attractor regulation and control method, device and equipment and a storage medium, and the method comprises the steps: constructing a Boolean network model, and determining a structure matrix L of a Boolean network; solving the power Ls of the network structure matrix L; solving the number Ns of Boolean network attractors; selecting a node given input from the Boolean network, and listing a single-point regulation and control strategy alternative table; and according to an attractor regulation and control demand target, an applicable single-point regulation and control strategy is preferably selected from the alternative table. According to the method, the calculation complexity of searching the Boolean network attractor is greatly reduced, the method is particularly effective when the network scale is very large, and the method has better engineering application value. 本发明提供了一种布尔网络吸引子调控方法、装置、设备及存储介质，所述方法包括：构建布尔网络模型，确定所述布尔网络的结构矩阵L；求解网络结构矩阵L的幂Ls；求解布尔网络吸引子的数量Ns；从布尔网络中选取